2001
DOI: 10.1046/j.1365-3016.2001.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of antibiotic use and associated infections in young children

Abstract: This study examines antibiotic usage and associated infections in infants and young children in Iowa. Longitudinal data were collected using a cohort recruited at birth from eight hospitals in eastern Iowa. Parents of recruited children were mailed questionnaires at 6 weeks, and 3, 6, 9, 12, 16, and 20 months of age. The cumulative incidence of antibiotic use and associated infections was determined using Kaplan-Meier survival analysis. There were data on 1,368 children. Antibiotic use was common in our cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…However, the significantly lower resistance of isolates from juveniles to enrofloxin in vitro may not justify its use in vivo , given the contraindicated use of enrofloxacin in growing animals (Norrby 1991). Additionally, the frequent use of cephalosporins in younger individuals (Bergus et al 2001) suggests that modifications in antibiotic usage patterns may have salutary effects on antimicrobial resistance patterns in adults.…”
Section: Effects Of Age and Sexmentioning
confidence: 99%
“…However, the significantly lower resistance of isolates from juveniles to enrofloxin in vitro may not justify its use in vivo , given the contraindicated use of enrofloxacin in growing animals (Norrby 1991). Additionally, the frequent use of cephalosporins in younger individuals (Bergus et al 2001) suggests that modifications in antibiotic usage patterns may have salutary effects on antimicrobial resistance patterns in adults.…”
Section: Effects Of Age and Sexmentioning
confidence: 99%
“…16 In early childhood, a high proportion of children get amoxicillin for the treatment of acute otitis media or other common childhood infections. 17 The aim of the present study was to investigate experimentally if simultaneous exposure to amoxicillin and NaF has potentiative effects on developing enamel in vitro. For this purpose, E18 mouse embryonic teeth were cultured in the presence of each agent alone or together at different concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that amoxicillin, the most common antibiotic used in childhood [1][2][3][4], is associated with developmental enamel defects accompanied by diffuse opacities, a condition known as molar-incisor hypomineralization (MIH) [5]. Hong et al [6] suggested a link between amoxicillin use during infancy and developmental enamel defect in permanent teeth and speculated that the critical time point for the effect of amoxicillin on ameloblasts was during the secretory stage.…”
Section: Introductionmentioning
confidence: 99%